2023
DOI: 10.22271/23940522.2023.v10.i2a.954
|View full text |Cite
|
Sign up to set email alerts
|

The impact of substituting waste flour from a broiler farm for commercial concentrate on production performance and edible offal of landrace pig

Abstract: The goal of the study was to determine how landrace pigs' production performance and edible offal would be affected by switching from commercial concentrate to waste flour from broiler farms (WFBF). There were three treatments and five replications in the study's fully randomized design. "The treatments were, A: using 24% commercial concentrate and 0% WFBW, B: 12% commercial concentrate and 12% WFBF, C: 0% commercial concentrate and 24% WFBF". Research variables: Production performance and edible offals of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It was also stated that by adding 12 kg of chicken farm waste-based concentrate to the finisher phase landrace pig ration, a reduction in body weight and digestive tract weight was achieved which was almost the same as the control (full commercial concentrate). Ariana (2023) [3] also presented the results of her research which showed that substituting the use of commercial pig feed concentrate with 50% concentrate from chicken farm waste could maintain the performance of landrace pigs and was almost the same as the control using 100% commercial concentrate. The results of the research above can provide information and facts on pig farms with alternative sources of feed ingredients that are cheap and can maintain production and do not reduce post mortem/postharvest results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also stated that by adding 12 kg of chicken farm waste-based concentrate to the finisher phase landrace pig ration, a reduction in body weight and digestive tract weight was achieved which was almost the same as the control (full commercial concentrate). Ariana (2023) [3] also presented the results of her research which showed that substituting the use of commercial pig feed concentrate with 50% concentrate from chicken farm waste could maintain the performance of landrace pigs and was almost the same as the control using 100% commercial concentrate. The results of the research above can provide information and facts on pig farms with alternative sources of feed ingredients that are cheap and can maintain production and do not reduce post mortem/postharvest results.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional content of the ration, the environment and handling of pigs before slaughter can affect slaughter weight and overall reduction in slaughter weight (Ariana et al, 2022) [2] . The use of cheap conventional feed and the addition of multiminerals to pig feed can increase performance in general (Sukmawati et al, 2022;Witariadi et al, 2023;Ariana, 2023) [17,21,3] . The lean cut (LC) percentage consists of the amount of meat in the 4 (four) main commercial cuts of ham, loin, Boston butt and picnic shoulder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation